2016
DOI: 10.1016/j.infbeh.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Do infants have the horizontal bias?

Abstract: A robust set of studies show that adults make more horizontal than vertical and oblique saccades, while scanning real-world scenes. In this paper we study the horizontal bias in infants. The directions of eye movements were calculated for 41 infants (M=8.40 months, SD=3.74, range=3.48-15.47) and 47 adults (M=21.74 years, SD=4.54, range=17.89-39.84) while viewing 28 real-world scenes. Saccade directions were binned to study the proportion of saccades in the horizontal, vertical and oblique directions. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Regarding the saccade orientations, we observe a strong horizontal bias in the adult group which is also consistent with previous studies [42], [43]. This horizontal bias can be explained by several factors, such as biomechanical factors, physiological factors and the layout of our natural environment [44]. Regarding biomechanical factors, Van Renswoude et al [44] stress the point that horizontal saccades require only the use of one pair of muscles whereas saccades in the other directions requires more than one pair of muscles [45].…”
Section: B Joint Distribution Of Saccade Orientations and Amplitudessupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the saccade orientations, we observe a strong horizontal bias in the adult group which is also consistent with previous studies [42], [43]. This horizontal bias can be explained by several factors, such as biomechanical factors, physiological factors and the layout of our natural environment [44]. Regarding biomechanical factors, Van Renswoude et al [44] stress the point that horizontal saccades require only the use of one pair of muscles whereas saccades in the other directions requires more than one pair of muscles [45].…”
Section: B Joint Distribution Of Saccade Orientations and Amplitudessupporting
confidence: 92%
“…This horizontal bias can be explained by several factors, such as biomechanical factors, physiological factors and the layout of our natural environment [44]. Regarding biomechanical factors, Van Renswoude et al [44] stress the point that horizontal saccades require only the use of one pair of muscles whereas saccades in the other directions requires more than one pair of muscles [45]. This horizontal bias is less obvious for young children, even though it may exist [44].…”
Section: B Joint Distribution Of Saccade Orientations and Amplitudesmentioning
confidence: 99%
“…To further increase the reliability of the data, fixations had a minimum duration of 100 ms and a maximum variance of 0.6° of visual angle. Only the fixation data are reported in this paper, and the saccade data from the FV task were published in van Renswoude et al ().…”
Section: Methodsmentioning
confidence: 99%
“…They are important in modeling adult eye movements (Foulsham & Kingstone, ), and they predict fixation locations above chance level (Tatler & Vincent, ). Recently, it was shown that infants also demonstrate the horizontal bias (van Renswoude, Johnson, Raijmakers, & Visser, ) and the central bias (van Renswoude et al, ). This indicates that infants, similar to adults, are more likely to fixate central locations and locations along the horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Saccade frequency, amplitude, and mean velocity are reduced and the velocity/amplitude distribution as well as the velocity profile become less skewed [9], [8]. An horizontal bias is also observed whatever the age, but is more pronounced when getting older [10]. Finally, the fixation durations decrease with age [8].…”
Section: Introductionmentioning
confidence: 94%